ANALYZING THE EFFECT OF BRAND FUNCTION ON CONSUMER RESPONSE TO COLORBOX BRAND IN MANADO - Lestari, Syevira Andirani; Saerang, David P.E; Pandowo, Merinda . (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Branding is very influential in the eyes of consumers and in general, brand can build consumer perception. Good branding also will encourage consumers to buy a product. If the consumers already feel the benefits of the product, they will support it by helping suggest those particular products to their relatives to experience it as well.The purpose of this research to analyze the effect of brand function on consumer response to Colorbox Brand that has been measured through guarantee, personal identification, social identification and status and to identify dimension of brand function that the most effect on consumer response to Colorbox Brand.This research uses causal type with a quantitative approach. The population of this study is the people who buy and use Colorbox brand products. The sample of this research is 100 respondents with data obtained through questionnaires.The finding of this research shows that guarantee and status are significantly effects consumer response to Colorbox brand. The contrary, personal identification and social identification is insignificantly effects consumer response. As the recommendation, the Colorbox companies have to maintain and improve the quality of the brand so that the company will receive positive response and will generate consumer royalty to the brand.Keywords: brand, brand association, consumer response